HAK-HAK ATAS TANAH DALAM SISTEM HUKUM PERTANAHAN DI INDONESIA MENURUT UNDANG-UNDANG POKOK AGRARIA (UUPA) - Indah Sari (JURNAL MITRA MANAJEMEN, 2017)
AbstractThis article wants to explain about Indonesia agrarian law system after the enactment of law no. 5/1960 about Agrarian Principles. The act focused on the unification of agrarian regulations in Indonesia to make our agrarian law system into a coherent unit. The Agrarian Principles shall assert that all people enjoy accesses to their land in order to guarantee their happiness and prosperity and also to bring justice for the people. It is stated at article 6 of the act that every plot of land should have its social function, means that it beneficiently producing good for the people. This article wants also to excersice whether The Agrarian Principles has guarantee a law assurance of rights over a portion of land for individual, state and member of costumary law. Keywords: Agrarian, Agrarian Law System, Law No. 5/1960 about Agrarian Principles